1995
DOI: 10.1016/0022-3115(94)00395-5
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of ceramic composites: forced CVI

Abstract: The submmed manuscript has been authored by a cmtractor of the Us. Government under contract No. M-AC05-840R21400. Accorcbngi~, the U.S. Govermnent retams a ~x c ! u s N B. royalty-frm license to p u M or reproduce the published form of connauaOn. or allow o m s to do so, for US. Government purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(13 citation statements)
references
References 2 publications
0
12
0
1
Order By: Relevance
“…Among the various fabrication processes, CVI is attractive process for the fabrication of SiC/SiC composites because it yields highly crystalline, near-stoichiometoric SiC fiber damage during processing is minimized. The forced flow thermal-gradient CVI (F-CVI) process is a further improvement since the low rates of producing and high porosity, which are the peculiar problem of CVI, are overcome [9]. Previous work by authors has reported on F-CVI process optimization of SiC/SiC composite with carbon (C) interphase including the effect of interphase thickness on tensile strength [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Among the various fabrication processes, CVI is attractive process for the fabrication of SiC/SiC composites because it yields highly crystalline, near-stoichiometoric SiC fiber damage during processing is minimized. The forced flow thermal-gradient CVI (F-CVI) process is a further improvement since the low rates of producing and high porosity, which are the peculiar problem of CVI, are overcome [9]. Previous work by authors has reported on F-CVI process optimization of SiC/SiC composite with carbon (C) interphase including the effect of interphase thickness on tensile strength [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In last decade, three main methods were developed: isothermal and isobaric CVI (ICVI) [18], forced CVI (FCVI) [19] and pressure-pulsed CVI (PCVI). In the case of the continuous gas-flowing chemical vapor deposition (CVD) or ICVI, thick films are easily formed on external surface of the porous substrates or the particle-packed beds.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental conditions are shown in Table I. Long CVI processing times are common 31,32 during the industrial fabrication of composites. However, in our study, short CVI processing times were used to keep the process pressure constant during the experiments.…”
Section: (3) Cvd CVI Experimentsmentioning
confidence: 99%